2021
DOI: 10.1021/acsami.1c19241
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Colloidal Particles Affect Colloidal Self-Assembly in Evaporating Self-Lubricating Ternary Droplets

Abstract: In this work, we unravel the role of surface properties of colloidal particles on the formation of supraparticles (clusters of colloidal particles) in a colloidal Ouzo droplet. Self-lubricating colloidal Ouzo droplets are an efficient and simple approach to form supraparticles, overcoming the challenge of the coffee stain effect in situ . Supraparticles are an efficient route to high-performance materials in various fields, from catalysis to carriers for therapeutics. Yet, the role of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…When the ouzo effect is dominated during LLPS, oil droplets disperse in the continuous phase of water. C-dots absorb at the surface of oil micro/nanodroplets and stabilizes them, 46 leading to the formation of nanopores in the final carbon film (Fig. 7(b), o-Cdots).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the ouzo effect is dominated during LLPS, oil droplets disperse in the continuous phase of water. C-dots absorb at the surface of oil micro/nanodroplets and stabilizes them, 46 leading to the formation of nanopores in the final carbon film (Fig. 7(b), o-Cdots).…”
Section: Resultsmentioning
confidence: 99%
“…The oil-to-particle ratio, size and surface properties of the assembled colloidal particles have been demonstrated to influence assembly structures. 45,46 Distinguished from previous reported assembled silica colloidal particles in the range of 10 to 1000 nm and graphenebased materials, 47,48 C-dots possess peculiar physical and structural features, including ultrasmall lateral dimension, a few layers of graphene sheets in-core structure and abundant surface functional groups. For example, surface oxides, such as carbonyl, carboxyl and hydroxyl groups, are the common species capping the carbon cores, enabling negative surface charge and high water solubility of C-dots.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…4 ) and fabricated mPEG-Coa as a AAL delivery carrier using polycation mPEG-PEAD and polyanion heparin. Here, PEGylation to polycations provides steric stability to the coacervate complex in a harsh environment [ 33 ] and their colloidal stability in aqueous conditions could be improved [ 14 , 15 ]. The enhanced stability of mPEG-Coa by PEGylation and its usefulness as an excellent growth factor carrier were demonstrated in our previous study, which suggested that the optimal range of PEG chain length for cation modification (MW 350) should be considered in ionic environments.…”
Section: Discussionmentioning
confidence: 99%
“…b) c) The beaker kept for 8 hrs in the humidity chamber at 60-70% relative humidity and temperature of 40°c ± 1°c. d) e) On removal from thermostat, oil separation was observed, if any [11].…”
Section: Methodsmentioning
confidence: 99%